Correlation between Serum Sialic Acid Level and frequent risk factors of Diabetic Retinopathy - Rashid, Nada F. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Diabetic retinopathy is an important complication of diabetes mellitus. It is supposed that elevated sialic acid in diabetes mellitus plays an important role in diabetic retinopathy. This study investigated serum total sialic acid levels related to glycemic control, blood pressure, retinopathy, and serum lipid level in diabetic retinopathy patients.Patients & Methods: Type 2 diabetic patients aged (56.47±10.68) years were recruited for the study. Fasting venous blood samples were collected from 132 diabetic subjects of whom 79 without retinopathy and 53 were diabetic with retinopathy. All the blood samples were processed for serum total sialic acid (TSA), fasting serum glucose (FSG), HbA1c, and lipid profile. Systolic and diastolic blood pressure was recorded by standard mercury sphygmomanometer.Results: Serum (TSA), FSG, HbA1c, triglycerides (TG), and LDL-cholesterol were increased significantly (P